Aspects of Management and Road Maintenance in Albania - Golgota, Alma; MSc. Diana Bardh, (European Journal of Multidisciplinary Studies, 2016)
Safety of road network is an essential part of economic and social development of any industrialized country. Decisions to maintain and improve the reliability, functionality and infrastructure structures can only be achieved through integrated planning and management life cycle routes. Always it has been a tendency to revise road maintenance strategies, but there is still a serious and reliable administration not only because of the shortage of funds, but also problems due to the reorganization of the system. Safety and performance of the road system depends on the continuous activity of road maintenance management. For it to be effective, it is necessary to intervene before depreciation has caused irreparable damages, or damages with a high economic cost of repairs. Investment in road infrastructure during 2006-2014 show that the life of these projects presents problems with maintenance and performance management life cycle in a wide range of component elements. Maintenance planning involves various problems that depend on the degree of degradation of the asphalt layers, the degree of deterioration of road structures (roads, tunnels, culverts, and economic planning of resources to repair them. The aim of this study is the first to provide a brief summary of the issues in the field of maintenance and management of the life cycle of investments in road infrastructure, proposing ways to reorganize the sector of management and maintenance of roads in the next and second testing and evaluation of the work and the nature of the standards are different types of road infrastructure projects, through a methodology consisting of a) development, b) collection of data, and c) analysis.
Keywords: Road Infrastructure, maintenance, depreciation, efficiency.